Optimalisasi Kinerja Karyawan Bagian Prodiksi PT. ABCD Melalui Stres Kerja dan Motivasi Kerja - Ramadhan, Faqih Fariz; Romi, Mochamad Vrans (J-MAS (Jurnal Manajemen dan Sains), 2024)
As time progresses, science and technology in every organization is required to have competent human resources. From the data obtained, there is a decline in employee performance. From several factors that affect employee performance, namely work stress and work motivation, the research objective is to determine the influence of work stress and work motivation on the performance of production department employees. The sample used consists of all production department employees, totaling 33 employees. This research employs a quantitative method with multiple regression data analysis using SPSS version 27. Data collection techniques involve interviews, questionnaires, and documentation. The results of this study indicate that work stress has a negative partial effect on employee performance. Work motivation has a positive partial effect on employee performance. Work stress and work motivation simultaneously affect employee performance.